Site diversity gain at the equator : radar-derived results modeling in Singapore - Yeo, Jun Xiang (2014)
Site diversity is an effective rain attenuation mitigation technique, especially in the tropical region where high rainfall rates are common. According to our previous study, site diversity gain is found to be dependent on the site separation distance and path elevation angle while it is independent of signal frequency, baseline angle and polarization angle. Therefore, using 28 months of Radar data, a simple site diversity gain prediction model is proposed. The proposed model is compared with the existing ITU-R models. The seasonal wind direction, another factor that might affect the site diversity gain prediction model, is shown to have negligible effect on site diversity gain. Triple-site diversity is also investigated and although it is found to provide gain improvement over dual-site diversity, this gain improvement is too little to justify for the cost of setting up an additional site. This study is useful for the implementation of site diversity as a rain attenuation mitigation technique in the tropical region.